Answer:
Graph 2.
Step-by-step explanation:
The graph is decreasing.
Hope this helps!
If not, I am sorry.
Subtract 4 from both sides of the equation.
y=-4-2x+2
add -4 and +2.
the answer is
y=-2x-2
Answer:
-12
Step-by-step explanation:
you have to divide 48 to (-4) and it equals to -12
so you multiply -12 to (-4) and it gives you 48
Y = x - 9 meets the y-axis at (0,-9)
y = -2x - 3 meets the y-axis at (0,-3)
This is because for every linear equation, there is a formula corresponding to it as y=mx + c, where (0,c) is where it meets the y-axis. As we assign the value of 0 to x, only c will be left to equal y, being the intercept.